System crash due to competition: a multiplex network simulation study - Pan, Lifan (Nanyang Technological University, 2022)
Throughout history, different systems has been continuously evolving. Even today, we have network systems in different fields interacting with one another, creating a complex structure with complex features. To better understand such diverse interactions, this projects looks into studying the competitive interactions between complex systems. Using Online Social Media Networks (OSN) as our case in point, parameters such as friend connections, risk tolerance, competitor influence are introduced to study its impacts on its network structure. The network simulation reveals that the system produces a “pseudo-steady” state despite having higher friend connections remaining and lower risk tolerance in a competitive environment. This signals that a competitor places heavy influence on a complex network structure as one of its factors for system crash. Finally, this project provides a more extensive look into one of the factors of a complex system crash analyzing how quickly a complex system can crash in a competitive environment. Subsequently also providing future recommendations to improve the simulations or investigate other factors.